Performance investigation on a thermal energy storage integrated solar collector system using nanofluid - Owolabi, A.L. (John Wiley and Sons Ltd, 2017)
The effect of Fe nanofluid on the performance enhancement on solar water heater integrated with thermal energy storage system is investigated experimentally. A 0.5 wt fraction of Fe nanoparticle was synthesized with the mixture of water/propylene-glycol base fluid. The experimental implementation utilized 40-nm-size Fe nanoparticle, 15 ° collector tilt angle, and 1.5 kg/min mass flow rate heat-transfer fluid circulation. The system efficiency reached 59.5 and 50.5 for with and without nanofluid. The water tank temperature was increased by 13 °C during night mode. The average water tank temperature at night mode was 47.5 °C, while the average ambient temperature was 26 °C. The Fe nanofluid improved the system working duration during night mode by an average of 5 h. The techno-economic analysis results showed a yearly estimated cost savings of 28.5 using the Fe nanofluids as heat transfer fluid. The embodied energy emission rate, collector size, and weight can be reduced by 9.5 using nanofluids. Copyright © 2016 John Wiley & Sons, Ltd. Copyright © 2016 John Wiley & Sons, Ltd.